BENTUK KEMITRAAN PADA KEGIATAN USAHATANI UBI KAYU DI DESA WUNDUWATU KECAMATAN ANDOOLO KABUPATEN KONAWE SELATAN - Dion Sarvega Daman; Anas Nikoyan; La Ode Kasno Arif (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
Indonesia, as an agricultural country, has great potential in developing cassava commodities, which are highly needed by industry and export. However, this sector currently faces capital and technological constraints, resulting in suboptimal productivity. Partnerships between farmers and companies have the potential to be a solution to this situation. The objective of this study is to ascertain the nature of partnership in cassava farming activities in Wunduwatu Village, Andoolo District, South Konawe Regency. Informants for this study were selected using purposive and snowball sampling techniques. Data were collected through observation, in-depth interviews based on interview guidelines, and documentation. The focus of this study is the form of partnership in cassava farming. The data analysis method used is qualitative analysis, which consists of three stages, namely data reduction, data presentation, and conclusion drawing. The results show that the form of partnership carried out by farmers in cassava farming in Wunduwatu Village is divided into two, namely core-plasma partnership and general trade partnership. Core-plasma partnerships are more structured, with technical and administrative arrangements through a memorandum of understanding (MoU), including land legality requirements and crop marketing procedures. Meanwhile, general trading partnerships are flexible and trust-based, without formal ties, and give farmers complete freedom in managing their farms.